IMPACT OF SEVOFLURANE AND ACETYLCYSTEINE ON ISCHEMIA-REPERFUSION INJURY OF THE LIVER FROM BRAIN-DEAD DONOR - A. E. Shcherba; S. V. Korotkov; A. F. Minov; Y. V. Slobodin; M. M. Savchuk; A. M. Dzyadzko; O. O. Rummo (Вестник трансплантологии и искусственных органов)
Aim. The purpose of our work was to estimate the impact of preconditioning with acetylcysteine and sevoflurane on ischemia-reperfusion injury of cadaveric donor liver with marginal features. Methods and results. In this prospective randomized controlled trial we recruited 21 heart beating donors with brain death. We assigned 11 donors to the study group, and 10 donors to the control group. Morphological characteristics of ischemia- reperfusion injury in both groups were analyzed. Conclusion. Use of pharmacological preconditioning with acetylcysteine and sevoflurane resulted in necrosis and hepatocyte apoptosis reduction as compared to the control group, thereby had a protective effect against ischemia-reperfusion injury.